Effects of exotic soybean genotype on growth performance, nutrient digestibility, and carcass traits in finishing pigs - Cao, H.; Hines, Robert H.; Gugle, Terry L.; Kropf, Donald H.; Moloney, C.A.; Jiang, J.M.; Cheng, J.Z.; Park, J.S.; Hancock, Joe D.; Schapaugh, William T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Compared to a corn-soybean meal control, added-fat from tallow, soybean oil, and dry-extruded whole soybeans (DEWS) improved ADG, F/G, and digestibility of DM and N. Feeding tallow increased belly firmness but also increased backfat thickness compared to diets with soy oil and DEWS. Comparisons among soybean genotypes indicated that high oleic acid soybeans supported greater growth performance than soybeans with high palmitic acid content. However, soybean genotype had no effect on carcass or meat quality measurements.
Keywords: Swine; Extrusion; Soybeans; Carcass; Finishing pigs